Mobile banking: concept and potential. (1st January 2003) - Barnes, Stuart J.; Corbitt, Brian
The internet and the mobile phone - two technological advancements that have profoundly affected human behaviour in the last decade - have started to converge. The products of this association are mobile data services. Using a variety of platforms, services are being created to enable mobile devices to perform many activities of the traditional internet, albeit in a reduced format for mobile devices. One area of activity is mobile (m-) banking (one of the first areas of commercial transaction on the wireless internet). Banking is an area that has extended in many different ways in recent years, including telephone and online banking. M-banking provides yet another channel for banking services, and in emerging markets, provides some possibility for becoming a primary channel. This paper examines the strategic implications of m-banking and the strategic positioning of m-banking services in different markets. The paper concludes with a discussion of the future for m-banking services.